Corruption: Laws, institutions, and values - Maira, Arun (2011)
The awareness of citizens about what is going on increases with advances in education, the growth of the middle class. The expansion of media and availability of information. Therefore, new institutional capabilities for representation and regulation are required along with growth. Moreover, the quality of the public discourse must improve too: to shift from ringing alarms to developing solution,and from mutual recriminations amongst citizens and institutions to a search for consensus. An ongoing social dialogue is necessary,amongst and in the various institutions that protect and represent citizens' interests, about the values we wish to live by and the society we want to shape. - Reproduced.
Keywords: Corruption